Opinion of doctors about unmet needs of rural diabetics - Dixit, Rohit; Pokala, Naveen (International Journal of Basic & Clinical Pharmacology, 2016)
Background: India is home to nearly 62 million diabetics - second only to China which has over 92 million diabetics. The main challenges for screening for diabetes and its complications in rural India are inadequate health care resources, lack of awareness and illiteracy among patients, limited physicians and paramedical staff trained in diabetes, lack of awareness among doctors as to who can legally practice diabetes in India. The present study was undertaken to explore the opinion of various doctors regarding diabetic care in rural India. Methods: The present study was conducted in Navodaya Medical College, Raichur and Mamata Medical College, Khammam. A cross-sectional study design was used to perform a multicentre survey from April 2015 to September 2015. Descriptive analysis was done using Statistical Package for Social Sciences (SPSS). Content and construct validation of the questionnaire was done by a panel containing subject experts, epidemiologists and a statistician. Following which the questionnaires were sent to different set doctors by print outs, email and via online survey tools. Results: All the doctors who were involved in the study had different opinion. MBBS doctors are more aware than BHMS/BAMS/BUMS doctors about the minimum degree required doing a diabetic practice legally in India. Both the group of doctors believed that the needs of diabetic population in rural India are not properly addressed; the reason behind this was lack of qualified doctors (according to majority of BHMS/BAMS/BUMS doctors) and lack of awareness among the rural patients (according to MBBS doctors). Both the doctors believe that MBBS doctors with some fellowship courses in diabetes can manage diabetes effectively (except serious complications). Conclusions: Both the doctors believe that MBBS doctors with some fellowship courses in diabetes can manage diabetes effectively (except serious complications). In India only MD (general medicine) and endocrinologists are technically qualified to treat diabetes. MCI should come forward and recognize the fellowship courses by regularizing them with proper guidelines and protocol set up for the institution providing such courses and allow those doctors to practice in rural areas, so that diabetics’ needs are addressed properly.